PENGARUH KEPEMIMPINAN, MOTIVASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PERUSAHAAN KONSTRUKSI - Tsauri, Sofiyan; Tjahyanti, Setia (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2022)
The purpose of this study was to determine the effect of variables such as leadership, competence, and working discipline on the performance of employee. The population in this study were employees of PT. XYZ, division of marketing and development. The sample was obtained through the total sampling method, which in according with the criteria amounted to 65 respondents. Data were collected through questionnaires to all respondents. Hypothesis testing in this study using Multiple Linear Regression analysis method. The results of this study indicate that leadership, competence, and working discipline have positive influence on employee performance. It can be said that the higher the leadership, competence, and working discipline, higher the level of performance given by each employee.